COMPARATIVE RESTORATION OF BALANCE AFTER DISTURBING THE VESTIBULAR APARATUS WITH PASSIVE WHOLE-BODY ROTATION: CASE STUDY - Ana Kašček; Matej Supej (Science of Gymnastics Journal)
The aim of this study was to establish whether the direction of the whole-body rotation influences the restoration of balance after the disturbance of vestibular apparatus with passive whole-body rotation. For this purpose, a chair powered by an electric motor was assembled. It rotates in a chosen direction for 10 seconds until it stops. It makes 11 turns in that time frame. The subject tested on the chair, is an active competitor of baton twirling. For baton twirling it is typical that the turns and pirouettes are performed in a counter clockwise direction (CCW). The results show that the direction of rotation influences the restoration of balance; the subject had better results in CCW rotation. COP (center of pressure) average in CW direction is 18.57% of time deviated to the left and 81.43% of time deviated to the right from center and in CCW direction is 53.83% of time deviated to the left and 46.17% of time deviated to the right from center in whole time of measurements. The differences in measurements depending on the direction of rotation and the deviation of the COP to the left and right of the center are significant.